Examining patient-reported late toxicity and its association with quality of life and unmet need for symptom management among nasopharyngeal cancer survivors: a cross-sectional survey - Tam, Victor C. W.; Ching, Jerry C. F.; Yip, Sindy S. T.; Kwong, Virginia H. Y.; Chan, Catherine P. L.; Wong, Kenneth C. W.; Lee, Shara W. Y. (Frontiers in Oncology, 2024)
Introduction: Alongside the improved survival of nasopharyngeal cancer (NPC), late radiation toxicities are alarmingly hampering survivors’ quality of life. A patient-reported symptom burden survey is lacking to address the unmet need for symptom management among local NPC survivors. Methods: A single-centre cross-sectional survey was conducted on 211 NPC survivors who had completed radiation therapy for three to 120 months. We employed the Chinese version M. D. Anderson Symptom Inventory - Head & Neck Module (MDASI-HN-C), Functional Assessment of Cancer Therapy - Head & Neck (FACT-HN-C), and a question extracted from the Cancer Survivors’ Unmet Needs Measure (CaSUN). Results: Two hundred valid responses were collected. Participants suffered from at least four moderate to severe symptoms (mean = 4.84, SD = 4.99). The top five severe symptoms were dry mouth, mucus problems, difficulty swallowing or chewing, teeth or gum problems, and memory problems. MDASI-HN-C subscales were negatively correlated with the physical, emotional, functional, and HN-specific domains of the FACT-HN-C. The unmet need for symptom management was positively associated with symptom burden, either general symptoms (Adjusted odds ratio [ORadj] = 1.566, 95% CI = 1.282 – 1.914, p < 0.001) or top-5 symptoms (ORadj = 1.379, 95% CI = 1.185 – 1.604, p < 0.001), while negatively associated with post-RT time (ORadj = 0.981, 95% CI [0.972, 0.991], p < 0.001). Conclusion: Virtually all NPC survivors suffer from late toxicities, which interplay with survivors’ perceptions intricately to affect their unmet needs for symptom management. Personalized supportive care strategies with regular assessments and stratifications are warranted.